The development of network error message alert retrieval for organizational intelligence system based on information retrieval techniques / Ahmad Syazwan Ahmad Zaki - Ahmad Zaki, Ahmad Syazwan (2015)
The error message from the NMS is only known by the network engineer to take action. But, for the top management they doesn‟t know the contents of the error message and what the important key word for them to understand the network problem exactly. The top management only wants to know the frequent problem occur in each location. From that information they can know what is the most problem occur in the network by each date or entire month for the future planning. In order to overcome this problem, this dissertation will develop an algorithm for the top management to retrieve the important information using information retrieval techniques and method. The experiment will be conducted based on the performance metrics which is accuracy and processing time. The result shows that, this algorithm archive 100% for the accuracy even though the input size is big. For the processing time, the result shows that if the input sizes become larger, the processing time also take effect and increasing in processing time.